Environmental impacts of cow-calf beef systems with contrasted grassland management and animal production strategies in the Massif Central, France. (May 2016) - Morel, Kevin; Farrié, Jean-Pierre; Renon, Julien; Manneville, Vincent; Agabriel, Jacques; Devun, Jean
Abstract: To meet the increasing market demand for store male calves sold in summer, cow-calf beef cattle producers from the Charolais area, France, can opt for various strategies including changing the calving period. The objective of our study was to analyze and compare the impacts on greenhouse gas emissions (GHG), energy consumption and land use of two grassland-based cow-calf beef systems in relation to their contrasted grassland management and animal production strategies. Based on repeated measurements over 2 years, we carried out a Life-Cycle Analysis on two systems designed on an experimental farm. The Aut-system was based on autumn-calvings that required budgeting for a sufficient quantity and quality of grass fodder stocks harvested to cover the high feed demands of winter-lactating cows. The Spr-system was based on spring-calvings so that the peak needs of the herd and the breeding cows coincided with peak pasture grazing period. Management of male calves relied on a more intensive use of concentrate in the Aut-system. This study showed that at identical beef live weight produced, the Spr-system required 18% more on-farm utilized agricultural area, excreted 14% more nitrogen and released 12% more enteric methane, but used 22% less mineral nitrogen fertilizer, 34% less fuel, 89% less off-farm fodder purchases, 73% less concentrate purchases and 5% less bedding straw purchases. Livestock emissions per animal were close between the two systems and accounted for 75% of gross GHG emissions. As the Aut-system had a higher animal productivity, it was able to dilute this impact at identical live weight produced (4% higher gross GHG emissions in the Spr-system). This higher productivity also enabled the Aut-system to use less land (13% higher land use in the Spr-system) but relied on greater use of inputs (31% lower energy consumption in the Spr-system). As the Aut-system involved a lower surface area to produce beef, it reduced the potential of carbon storage by grassland to offset gross GHG emissions. This is the reason why the Spr-system led to 9% lower net GHG emissions. This mixed bag of results raises the question of the relative weight lent to each environmental impact and of the complementarities between strategies in grassland-based systems at region-wide scale. Highlights: Two grassland-based cow-calf beef systems with contrasted strategies are compared. The spring-calving system releases 4% more gross greenhouse gases to produce beef. The spring-calving system releases 9% less net greenhouse gases to produce beef. The spring-calving system uses 31% less energy to produce beef. The spring-calving system uses 13% more land to produce beef.